Selected Urban legends prevalent in Ranchi as Campus Lore - Sada Suman Tudu, R K Archana; Sarma, Rabindranath (International Journal of Psychosocial Rehabilitation, 2019)
Campus lore is the term used to describe the narratives with composition of cultural element like myths, stories, and traditionsthat have developed on college or university campuses. Campus lore is a one sort among the eleven, recognised by J H Brunvand as Urban Legends.Urban legends are stories in a current setting that are recounted as actual individual experiences but include conventional variants that show their legendary character are the easiest subject in which the student may see the development of legends.This paper will try to elaborate about the term campus lore and urban legends and will explain the campus lores found in the Ranchi district.The data has been composed by both the primary and secondary sources.